Influence of probiotics on rat liver biotransformation enzymes - Matuskova, Zuzana; Tunkova, Alena; Anzenbacherova, Eva; Zidek, Zdenek; Tlaskalova-Hogenova, Helena; Anzenbacher, Pavel (Neuro endocrinology letters, 2009)
OBJECTIVES: The aim of the study was to find, whether probiotic Escherichia coli Nissle 1917 O6:K5:H1 (EcN) influence the amount and activity of cytochromes P450 (CYP) in rat liver. DESIGN: Live bacterial suspension of EcN was applied to the female Wistar rats in single dose or for 14 days consecutively. The bacterial lipopolysaccharide (LPS) isolated by phenol extraction from the EcN was given to the rats for 14 days as well. Control rats were treated with the saline solution daily for 14 days. Relative amount of CYP2C6, CYP2C9 (corresponding to rat CYP2C11), CYP3A1 and CYP1A2 protein expression in rat liver microsomes was determined by Western blotting. For the determination of six CYP activities (corresponding to human CYP1A2, CYP2A6, CYP2B6, CYP3A4, CYP2C9 and CYP2D6) fluorescence, luminescence or absorbance detection was used. RESULTS: The data presented show that the changes of the total content of the CYP enzymes in rat liver are not significant after administration of the probiotic for 1 or 14 days as well as of the LPS. Western blots revealed a slight increase in CYP2C6 protein expression; level of another rat CYP2C protein (readings with anti-human CYP2C9 antibody corresponding to the rat CYP2C11) as well as of CYP1A2 was elevated after administration of LPS; a small decrease was observed with CYP3A1 protein. Changes in activities of CYP forms are not significant, only the activity of rat CYP2C forms in liver microsomal samples of rats given free LPS appeared to exhibit a small, but significant tendency to increase. CONCLUSION: The results show that the p.o. administration of probiotics to rat does not markedly influence the rat hepatic CYP enzymes.
Keywords: játra; lipopolysacharidy; Lipopolysaccharides; Female; Blotting, Western; Time Factors; krysa rodu Rattus; zvířata; potkani Wistar; časové faktory; Cytochrome P-450 Enzyme System; ženské pohlaví; Liver; Rats, Wistar; probiotika; Rats; Animals; western blotting; Probiotics; systém (enzymů) cytochromů P-450